Contraception with estradiol valerate and dienogest: adherence to the method - Fruzzetti F; Paoletti AM; Fidecicchi T; Posar G; Giannini R; Gambacciani M (Dove Medical Press, 2019)
Franca Fruzzetti,1 Anna Maria Paoletti,2 Tiziana Fidecicchi,1 Giulia Posar,1 Riccardo Giannini,3 Marco Gambacciani11Department of Obstetrics and Gynecology, Pisa University Hospital, Pisa, Italy; 2Department of Obstetrics and Gynecology, Cagliari University Hospital, Cagliari, Italy; 3Department of Surgical, Medical, Molecular Pathology and Critical Area, University of Pisa, Pisa, ItalyPurpose: The aim of the study was to examine the discontinuation rate of hormonal contraception with estradiol valerate (E2V) and dienogest (DNG).Patients and methods: We collected data at the Family Planning Clinics of the Departments of Obstetrics and Gynecology of Pisa and Cagliari. We included in the analysis 354 consecutive women using oral contraceptive pills containing E2V and DNG. We analyzed the rate and the reason for discontinuation, classifying the reasons in 5 categories: 1) minor side effects, 2) adverse events, 3) other events not directly caused by the drug or conditions for which the pill could represent a risk factor, 4) no compliance with the method and 5) no further need.Results: Of the 354 women examined, 50.8% had discontinued E2V/DNG pill. Excluding women who stopped the pill because of no further need (10.5%), 27.4% discontinued because of minor side effects, 1.7% discontinued for adverse events, 9.9% because of other events not directly caused by the drug or conditions for which the pill could represent a risk factor and 1.4% because of difficulties with compliance. Irregular bleedings were the main reasons reported for discontinuation. The time to discontinuation for irregular bleedings was significantly (p<0.02) longer in adults than in adolescents and slightly but not significantly longer in women who received information about this possible effect.Conclusion: Unacceptable cycle control was the principal cause of discontinuation of pill with E2V and DNG. An appropriate information about this possible effect may improve adherence to this combined oral contraceptive.Keywords: estradiol valerate, hormonal contraceptives, irregular bleedings, dienogest